Effect of anti-SARS-CoV-2 BNT162b2 mRNA vaccination on thrombin generation in children with inflammatory bowel disease - Stercel, Vivien; Lóczi, Linda; Kadenczki, Orsolya; Nemes, Éva; Nagy, Béla; Hodossy-Takács, Rebeka; Szabó, Attila Ádám; Fagyas, Miklós; Kappelmayer, János; Szabó, Tamás; Bagoly, Zsuzsa (Frontiers in Immunology, 2023)
Background: Inflammatory bowel disease (IBD) including Crohn’s disease (CD) and ulcerative colitis (UC), are associated with higher thrombotic risk and enhanced thrombin generation (TG) in adults. Despite encouraging data reporting vaccine safety and low IBD flare rates in adults with IBD, vaccine hesitancy was demonstrated to be high in families of children with IBD. We aimed to find out whether TG is increased in children with IBD as compared to healthy controls and whether TG parameters show significant changes following SARS-CoV-2 mRNA vaccination. Patients and methods: In this observational case-control study, 38 children with IBD (CD:18, UC: 20) aged 12-18 years and 62 healthy age-and sex-matched children were enrolled. Blood was collected before the first dose and 2-6 weeks after the second dose of BNT162b2 (Pfizer-BioNTech) mRNA vaccine dose. Blood cell counts, fibrinogen, inflammatory markers (hsCRP, ferritin), anti-SARS-CoV-2 antibody levels were investigated, TG assay was carried-out using platelet-poor plasma. Detailed clinical parameters including disease activity scores (PUCAI, PCDAI) were registered pre- and post-vaccination. A guided questionnaire was used to collect data on adverse reactions (AEs) post-vaccination. Results: Baseline TG parameters did not differ between patients and controls. Endogenous thrombin potential showed a significant positive correlation with markers of inflammation and with PCDAI. Inflammatory parameters and TG did not increase in patients and controls pre- and post-vaccination. Vaccination significantly increased antibody levels in all three investigated groups, but post-vaccination anti-SARS-CoV-2 S IgG/IgM levels were below the 5th percentile value of healthy children in more than one third of patients. Those receiving TNF inhibitor therapy presented significantly lower SARS-CoV-2 S IgG/IgM levels as compared to patients on other immunosuppressive regimens. Systemic AEs did not differ between patients and controls while lower rate of local symptoms was found post-vaccination in children with IBD. Only 2 IBD flares were detected 2-6 weeks after the second dose of vaccination. Conclusion: Our study is the first to support the safety and efficacy of anti-SARS-CoV-2 BNT162b2 vaccination in children with IBD with detailed pre-and post-vaccination laboratory data including TG. Results of this study may further increase confidence and reduce vaccine hesitancy in caretakers of pediatric IBD patients.